Amorphous calcium carbonate (ACC) cement for ground improvement - Zhang, Zheng (2025)
This paper presents a new method of using amorphous calcium carbonate (ACC) cement for ground improvement. Drawing inspiration from the mineralization processes observed in marine organisms, a process has been developed to produce ACC-cement using waste carbide sludge and carbon dioxide. The ACC-cement in the powder form can be mixed with soil and subjected to further microbially induced carbonate precipitation (MICP) process to transfer ACC into other more stable form of CaCO3 crystals such as calcite. This study showed that by mixing 2.5% (weight to weight) of ACC with sand and subjecting the mixture to a cyclic cementation solution treatment for three days, the compressive strength of treated sand increased to 9 MPa. A microscopic analysis demonstrated the transformation of nano-sized ACC into rounded vaterite, and then rhombohedral calcite that bonded sand grains together to promote effective interlocking between sand particles. The use of ACC also led to a much faster strength gain than the use of cement.